Genetic predictors of outcomes of assisted reproductive technology - I V Vladimirova; E A Kalinina; A E Donnikov (IP Berlin A.V., 2014)
Variability in the subfertile patient population excludes the possibility of a single approach to controlled ovarian stimulation. Genetic screening may allow an individual patient's response to stimulation during controlled ovarian stimulation to be predicted based on genotype. The objective of the study was to analyze the specific features of folliculogenesis, oogenesis, and embryogenesis in patients in relation to single nucleotide polymorphisms in assisted reproductive technology.